Impact of leadership styles on faculty performance: Moderating role of organizational culture in higher education - Amna Rasool Jamali; Arabella Bhutto; Mahvish Khaskhely; Waqar Sethar (Management Science Letters, 2022)
There are many leadership styles, which have different impacts on employees' performance. In higher education, faculty performance depends on many factors including Leadership style & Organizational culture. This study aims to examine the effect of leadership styles on faculty performance (FP) and more specifically to examine the moderating effect of Organizational Culture in the association between leadership styles and faculty performance in higher education institutions (MUET, Jamshoro). This study used quantitative methodology to identify the leadership styles which exist in MUET, Jamshoro, and their impact on faculty performance with organizational culture as moderator. It used both the sampling techniques probability and non-probability, and the sample size was 384 and the data was analyzed in SmartPLS 3. For leadership style, Full Range Leadership Model was adopted and for organizational culture, Competing Value Framework (CVF) was used. This study found that Transformational (TF) leadership has a positive significant relation with faculty performance at MUET, Jamshoro. And Organizational Culture (OC) as moderator negatively moderates the relation between Laissez-faire (LF) leadership and faculty performance (FP). According to faculty, transformational leadership is best suited to promote their performance on account of giving them challenging work, autonomy, mutual trust, through supporting subordinates' creativity, improving their confidence, and maintaining collaborations. Laissez-faire leadership also exists in an academic institution and has a positive impact on faculty performance. However, Transactional leadership has a negative impact on faculty performance. The future study could be conducted in other universities, or a comparison of leadership styles can be made between public and private universities with different models of leadership style and with different organizational culture models.